S95 Prolonged neutrophil dysfunction and phenotype in elderly hospitalised community acquired pneumonia patients. (11th November 2022) - Faniyi, AA; Thein, OS; Belchamber, KBR; Parekh, D; Scott, A; Sapey, E; Thickett, DR
Abstract : Background: Community acquired pneumonia (CAP) is a leading cause of morbidity and mortality in older patients. Neutrophils from elderly CAP patients have an activated phenotype and migrate inaccurately towards IL-8. We have previously demonstrated that the dysfunctional chemotaxis of neutrophils in elderly CAP patients persists, despite patient recovery from the initial episode (Sapey et al., 2017; PMID: 28657793). This change in neutrophil phenotype and functional paralysis is not fully understood but can make patients more susceptible to a secondary CAP episode. We hypothesise that neutrophil phenotype in CAP persists and contributes to long term dysfunction. Methods: CAP patients admitted to the Queen Elizabeth Hospital, Birmingham, confirmed negative for COVID-19 (n=16) over 50 years old were recruited. From this cohort, 5 patients were followed up after a minimum of 6 weeks ( table 1 ). Peripheral Neutrophils were isolated by Percoll density centrifugation at baseline and follow up. Chemotaxis towards IL-8, phagocytosis of Streptococcus pneumoniae and expression of cell surface markers were assessed. Results: There was no difference in the speed of migration (p=0.483), accuracy of migration (p=0.432) or chemotactic index (p=0.870) of neutrophils from CAP patients at baseline and follow up. Phagocytosis of S. pneumoniae was also similar at baseline and follow up (p=0.438). The median fluorescence intensity (MFI) of CD10 (p=0.188), CD16 (p=0.625), CXCR4 (p=0.625), CD62L (p=0.813), CD11b (p=0.438), CD66b (p=0.313), PD-L1 (p=0.813) and CD11c (p=0.313) were also unchanged at follow up. However, there was a reduction in MFI of CD54 (p=0.063) and CXCR2 (p=0.063), and an increase in the percentage of CXCR4+ cells (p=0.063) at follow up, although these were not significant. Conclusion: In this cohort of elderly CAP patients, we have confirmed that the key effector neutrophil function of migration does not improve or worsen after clinical recovery. There is also no improvement in phagocytosis. In addition, surface expression of most neutrophil markers was unchanged at follow up. The reduction in MFI of CD54 and CXCR2 and increase in percentage of CXCR4+ cells suggest a change in phenotype from reverse transmigration and upregulation of IL-8 receptor to a senescent phenotype. However, these will require validation in a larger cohort. Please refer to page A211 for declarations of interest related to this abstract.